Preparation and sports performance of multilayer flexible anti stabbing fabric martial arts sports composite conjugate materials - Zhang, Jie; Ding, Huanxiang; Wang, Yanqun (Frontiers in Chemistry, 2023)
Puncture-resistant clothing plays an important role in martial arts. This article studies the preparation process of multi-layer flexible stab-resistant fabrics, analyzes the sports properties of the fabric, and explores the potential application of stab-resistant clothing in martial arts. This article uses ultra-high molecular weight polyethylene fiber as raw material, preprocesses it, including fiber cleaning, drying, lamination, and laminating them together through needle punching, then soaks the laminated fibers in resin, and the soaked fibers solidifies to form a specific flexible puncture-resistant fabric. This article prepares three types of layered fabrics, namely woven fabrics, nonwoven materials, and composite materials of nonwoven materials + woven fabrics + nonwoven materials, and analyzes the kinematic characteristics of the three layered fabrics. Experimental results show that when the number of layers is 4, the average breaking tensile forces of woven fabrics, nonwoven materials and composite materials are 3400, 4600 and 3860 respectively, and the average breaking elongations are 11.8%, 40.6% and 17.4% respectively. This shows that woven fabrics have the highest levels of air permeability and moisture permeability.